2010
DOI: 10.3109/0886022x.2010.516853
|View full text |Cite
|
Sign up to set email alerts
|

Coffee, nutritional status, and renal artery resistive index

Abstract: Background: The relationship between nutrition and atherosclerosis is known, even dissociated from protein malnutrition. Cardiovascular impact of several nutrients is known; among them the action of coffee is still debated and cardiovascular effect of caffeine has been investigated without definite results. Objective: The aim of this study is to investigate whether coffee habits, and/or quantity of coffee consumption, have any relationship with renal resistive index (RRI), a hallmark of arterial stiffness (AS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
0
19
2
1
Order By: Relevance
“…According to recent studies, a protective effect of coffee on fatty liver can be linked with kidney function through insulin sensitivity. 22,23 Our study results differ from previous ones with regard to ALT. There was no significant relationship between coffee and ALT.…”
Section: Discussioncontrasting
confidence: 84%
“…According to recent studies, a protective effect of coffee on fatty liver can be linked with kidney function through insulin sensitivity. 22,23 Our study results differ from previous ones with regard to ALT. There was no significant relationship between coffee and ALT.…”
Section: Discussioncontrasting
confidence: 84%
“…Mean eGFRs were higher in coffee drinkers in four studies, [8][9][10]12 lower in one study 14 and the same in two studies. 11,13 Overall, there was no difference in eGFR (MD 0.44 mL/min; 95% CI −3.34 to 4.21), but there was significant heterogeneity (I 2 =93.9%). One study was methodologically distinct with a 10-year age difference between coffee drinkers and non-drinkers.…”
mentioning
confidence: 97%
“…We investigated statistical heterogeneity by calculating I 2 , and examined the effect on I 2 of excluding studies with significant methodological differences. All analyses were performed using the metafor package in R. 7 Seven studies reported cross-sectional eGFRs according to coffee consumption, [8][9][10][11][12][13][14] including three from Wijarnpreecha et al 10,11,13 One study 8 reported adjusted MDs, and we calculated crude MDs from the others. The results are shown in Figure 1.…”
mentioning
confidence: 99%
“…In this dietary context, the use of coffee is of benefit for arterial hypertension through some renal mechanism [45,46] and for fatty liver through the increase of insulin sensitivity [47]. Multiple lifestyle behaviors have effects on health risks like obesity and other health outcomes.…”
Section: Mediterranean Diet: Food Recipes and Cookingmentioning
confidence: 99%